Stochastic resonance in nuclear fission - Berezovoj, V.P.; Bolotin, Yu.L.; Dzyubak, A.P.; Yanovsky, V.V.; Zhiglo, A.V. (Вопросы атомной науки и техники, 2001)
Fission decay of highly excited periodically driven compound nuclei is considered in the framework of Langevin approach. We used residual-time distribution (RTD) as a tool for studying the dynamic features in the presence of periodic perturbation. The structure of RTD essentially depends on the relation between Kramers decay rate and the frequency w of periodic perturbation. In particular, the intensity of the first peak in RTD has a sharp maximum at certain nuclear temperature depending on w. This maximum should be considered as fist-hand manifestation of stochastic resonance in nuclear dynamics.